Tipe Kepribadian Berhubungan dengan Perilaku Caring Perawat - Jek Amidos Pardede; Masri Saragih; Marthalena Simamora (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to determine the relationship between personality types and nurses' caring behavior at the Porsea Regional Hospital. The research design used is correlation analytic with the cross-sectional approach. This study's results are introverted personality types with good caring majority behavior, 62.2%, and extrovert personality types with good caring majority behavior 94.3%. Statistical test results showed a significant relationship between personality types and nurses caring action at the Porsea Regional Hospital (p = 0.010; p <0.05). In conclusion, the majority of nurse personality types have an extroverted personality, and the majority of nurse caring behavior has good caring practice. There is a relationship between personality type and caring nurse behavior. Keywords: Nurse, Caring Behavior, Personality Type